A first-in-human study investigating biodistribution, safety and recommended dose of a new radiolabeled MAb targeting FZD10 in metastatic synovial sarcoma patients - Giraudet, Anne-Laure (BMC Cancer, 2018)
BACKGROUND: Synovial Sarcomas (SS) are rare tumors occurring predominantly in adolescent and young adults with a dismal prognosis in advanced phases. We report a first-in-human phase I of monoclonal antibody (OTSA-101) targeting FZD10, overexpressed in most SS but not present in normal tissues, labelled with radioisotopes and used as a molecular vehicle to specifically deliver radiation to FZD10 expressing SS lesions. METHODS: Patients with progressive advanced SS were included. In the first step of this trial, OTSA-101 in vivo bio-distribution and lesions uptake were evaluated by repeated whole body planar and SPECT-CT scintigraphies from H1 till H144 after IV injection of 187 MBq of (111)In-OTSA-101. A 2D dosimetry study also evaluated the liver absorbed dose when using (90)Y-OTSA-101. In the second step, those patients with significant tumor uptake were randomized between 370 MBq (Arm A) and 1110 MBq (Arm B) of (90)Y-OTSA-101 for radionuclide therapy. RESULTS: From January 2012 to June 2015, 20 pts. (median age 43 years [21–67]) with advanced SS were enrolled. Even though (111)In-OTSA-101 liver uptake appeared to be intense, estimated absorbed liver dose was less than 20 Gy for each patient. Tracer intensity was greater than mediastinum in 10 patients consistent with sufficient tumor uptake to proceed to treatment with (90)Y-OTSA-101: 8 were randomized (Arm A: 3 patients and Arm B: 5 patients) and 2 were not randomized due to worsening PS. The most common Grade ≥ 3 AEs were reversible hematological disorders, which were more frequent in Arm B. No objective response was observed. Best response was stable disease in 3/8 patients lasting up to 21 weeks for 1 patient. CONCLUSIONS: Radioimmunotherapy targeting FZD10 is feasible in SS patients as all patients presented at least one lesion with (111)In-OTSA-101 uptake. Tumor uptake was heterogeneous but sufficient to select 50% of pts. for (90)Y-OTSA-101 treatment. The recommended activity for further clinical investigations is 1110 MBq of (90)Y-OTSA-101. However, because of hematological toxicity, less energetic particle emitter radioisopotes such as Lutetium 177 may be a better option to wider the therapeutic index. TRIAL REGISTRATION: The study was registered on the NCT01469975 website with a registration code NCT01469975 on November the third, 2011.